"Is nicht egal": Guided Multimodal Reading of a Music Video Advertisement. Issue 1 (6th May 2020) - Benjamin, John D.; Donohue‐Bergeler, Devon; Fuchs, Katrin; Lorenz, Alexander
Abstract: This case study addresses the language‐culture divide contributing to curricular bifurcation in many collegiate language departments and presents a lesson plan to help language instructors bridge the gap. The lesson on public transportation is designed for first‐semester second language (L2) German students and focuses on a guided reading of a music video advertisement – the Berliner Verkehrsbetriebe (BVG) spot "Is mir egal, " featuring Kazim Akboga (2015). The instructor and the L2 learners, using these guided reading strategies (Kern, 2000; Paesani, Allen, & Dupuy, 2016), collectively unpack the text and make meaning – culturally, linguistically, and in‐between. This article presents data in the form of written student reflections on the video advertisement and guided reading strategies as well as instructor observations. The lesson is designed according to the FLLITE Project (Foreign Languages and the Literary in the Everyday, https://fllite.org/ ), dedicated to the free use of the Open Educational Resources (OER) movement, thus allowing instructors to adapt it to their specific needs.